Chirocephalus sanhadjaensis sp. nov., a new chirocephalid species (Branchiopoda: Anostraca) from Numidia (Algeria) - Boumendjel, Lylia; Rabet, Nicolas; Amarouayache, Mounia (Zootaxa, 2018)
A new species of Chirocephalus collected in temporary freshwater ponds in Northeastern Algeria is described. Chirocephalus sanhadjaensis sp. nov. seems to be restricted to Ain-Magroun and Belkroun pools (Skikda Province). The most similar species is C. marchesonii Ruffo & Vesentini, 1957, which is endemic to Italy. The new taxon, belonging to the “diaphanus” species group of the genus Chirocephalus, is identifiable from all congeners primarily by the shape of the antennal appendages and that of the apex of the distal antennomere of the antennae. The resting eggs of C. sanhadjaensis sp. nov. are similar to those of C. diaphanus or C. salinus but are larger (448.24 ± 30.93 µm). The restricted distribution of this species confirms the high biological diversity of the area of the Guerbes-Sanhadja eco-complex.